The effects of 8 weeks of dynamic hamstring stretching or nordic hamstring exercises on balance, range of motion, agility, and muscle performance among male soccer players with hamstring shortness: a randomized controlled trial - Elham Hosseini; Mohammad Alimoradi; Mojtaba Iranmanesh; Farzaneh Saki; Andreas Konrad (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background This study investigated the effects of an eight weeks exercise regimen with either Nordic hamstring exercises or dynamic hamstring stretching (DHS) on balance, range of motion, agility, and muscle performance in male soccer players with hamstring shortness. Methods Sixty participants were divided into three groups: NHE (n = 20), DHS (n = 20), and control (CO; n = 20). The NHE group performed Nordic hamstring exercises, the DHS group engaged in dynamic stretching, and the CO group did not receive any intervention. Assessments were conducted before and after the interventions using active knee extension test (AKET), sit-and-reach test (SR), Y-balance test (YBT), Illinois agility run test (IAT), and countermovement jump test (CMJ). Results The results showed significant improvements in measured parameters for both the NHE (AKET: 16.16%; SR: 11.33%; YBT: 16.25%; IAT: 12.84%; CMJ: 7.28%) and DHS (AKET: 2.17%; SR: 5.51%; IAT: 4.54%; CMJ: 1.26%) groups, while no significant changes were observed in the CO group (p ≤ 0.001). The NHE group demonstrated superior effects compared to the DHS and CO groups, except for the countermovement jump test. Conclusion The findings suggest that including NHE in training regimens is recommended, particularly for soccer players with hamstring shortness. Therefore, both NHS and DHS positively influenced performance, range of motion, balance, and agility. However, NHE proved to be more effective, yielding more improvements that are significant across the performance, range of motion, balance, and agility parameters. Trial registration This trial was registered at Iranian Registry of Clinical Trials (Identifier: IRCT20230612058457N3) on April 7, 2024.